Teaching to design educational technologies. (1st January 2011) - Kali, Yael; Ronen-Fuhrmann, Tamar
Finding ways to support novice educational technology designers is of high importance in many design fields. In this research we examined three courses in which graduate students learned to design technology-based curriculum modules. The courses were based on a teaching model developed in a design-based research methodology with four iterations. The model integrates the openness of a studio approach, with the structure of a well-known instructional systems-design process. It also takes advantage of experts' design knowledge embedded in a database of design principles. Qualitative data was used to evaluate the affordances and challenges of progressive versions of the teaching model. A generalised model for teaching educational technology design was derived, in which the following constructs are intertwined: a structuring the design process b building on accessible repositories of expert design knowledge c enabling dialogic learning.